RFID Demystified: Part 1. The technology, Benefits and Barriers to Implementation - Wilding, Richard D.; Delgardo, Tiago (The Chartered Institute of Logistics and Transport, 2004)
Radio Frequency Identification (RFID) has by some commentators been heralded as a technology that will have as big an impact on supply chain operations as the advent of computer based planning systems in the early 1970’s. Whereas others say it is just yet another technology fad that in a couple of years will have gone away. We are continually reading conflicting messages about RFID, this is partly due to the term being miss used in some quarters and also because as with all new technologies it takes time for all those involved to define a common language. In this series of articles we hope to demystify the technology and its applications. RFID demystified part 1 will cover the technology and its benefits and possible barriers to implementations. Part 2 will progress to give an overview of the potential applications of the technology and finally part 3 will present an overview of the cases where the technology has been applied. Trials have been undertaken by a variety of organisations including Benetton, Woolworths, Scottish Courage and Figleaves.com to name a few. Each article also includes a series of references and a bibliography which it is hoped will enable both practitioners and academics the opportunity to investigate the areas in more depth if this is required.